Efektivitas Simulasi Kartu Role-Playing dalam Pemahaman Kebersihan dan Sanitasi Pangan Mahasiswa Kuliner - Amalia Akita; Roni Gunawan; Jenita Oktavia Panjaitan; Karl Fritz Pasaribu (Pusat riset dan Inovasi Nasional, 2025)
Food hygiene and sanitation are crucial in the culinary industry to prevent contamination and protect consumer health. However, foodborne diseases remain a global issue due to poor food handling practices. Traditional lecture methods are often ineffective in improving students' practical skills related to food safety. This study evaluates the effectiveness of Role-Playing Cards as an interactive learning tool. A quasi-experimental design with a pre-test and post-test was conducted on 70 culinary students enrolled in a food hygiene and sanitation course. Participants were divided into two groups: Cross-Contamination and Foodborne Illness. The findings showed a significant improvement in understanding, with post-test scores increasing from 58.2 to 87.6 (p < 0.001) and from 60.4 to 89.2 (p < 0.001). Additionally, 99% of students found the method relevant, and 97% considered Role-Playing Cards engaging and easy to apply. In conclusion, this method effectively enhances students' understanding, promotes critical thinking, and provides a more interactive learning experience in food safety education.